2004
DOI: 10.1007/s00216-003-2227-0
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro assays for determination of oestrogenic activity

Abstract: At present, in-vitro bioassays are predominantly being seen as tools to identify, through screening programs, whether or not individual chemical compounds have an effect on the endocrine system. However, as the techniques mature, they are likely to find use in the future in monitoring of discharges to the environment for any biological effect and will compliment the range of chemical and biological techniques also available for monitoring environmental quality. Such an approach has already been utilised by a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Animal testing is also undesirable and expensive. The E-SCREEN assay used in this study measures MCF-7 cell growth and is recognized as valid for large-scale screening, reliable, easy, and quick to perform [22,23,37].…”
Section: Estrogenic Characteristics Of Manuka Steinmentioning
confidence: 99%
“…Animal testing is also undesirable and expensive. The E-SCREEN assay used in this study measures MCF-7 cell growth and is recognized as valid for large-scale screening, reliable, easy, and quick to perform [22,23,37].…”
Section: Estrogenic Characteristics Of Manuka Steinmentioning
confidence: 99%
“…General reviews on this topic are not common. Review papers involving in vitro assays are quoted for the two major diseases reported herein, namely, cancer and HIV. , It is important to note that the toxicity of the inhibitor toward a human cell line is also reported. This gives an indication of the selective nature of the inhibitor.…”
Section: Experimental Bioactivities Of Enzyme/inhibitor Interactionsmentioning
confidence: 99%
“…Various in vitro bioassays exist, usually relying on transgenic bioengineered cells (yeast or breast cancer cells) that connect an estrogen receptor from humans or more a sensitive fish like trout, to express a measurable response. These bioassays may be broadly categorized as 1ligand-binding assays where an ER is connected to a promoter that produces a measurable luminescence or colormetric response (2) immunoassays where the ERE to bind with DNA, modulating transcription of target genes causing a measurable response, and (3) cell proliferation assays where the number of cells in indicative of estrogenicity (Scrimshaw and Lester, 2004).…”
Section: In Vitro Single Cell Bioassaysmentioning
confidence: 99%